Study of Suppression of Diffracted Multiples from Steep Slope Zones in Deep Water. Issue 6 (November 2013) - Song‐Lei, XIE; Yi‐Ke, LIU; Yi‐Bo, WANG; Xu, CHANG; Peng, LI; De‐Gang, JIN
Abstract In areas with steep slope zones in deep water and rugged seafloor, even using long acquisition cable, the reflected point out of the cable length, because of the variable direction of propagation of diffracted multiples. It makes diffracted multiple prediction without sufficient near offset or negative offset information, so that we cannot predict and suppress diffracted multiples exactly. This has been a big problem for us in suppression of diffracted multiples from steep slope zones in deep water. This paper presents a new method based on the feedback iteration model, introduces the adjacent shot record into the feedback iteration model, to supplement the near offset and negative offset data information. Tests on the Sigsbee2b model and real data show that this method can suppress well the diffracted multiples associated with the free surface of steep slopes in deep water.